SINGKONG PATIENT OF FORMULATION (Manihot Utillisima) AND GELATIN ON PHYSICOCYMIC AND ORANOLEPTIC PROPERTIES OF MARSHMALLOW - ., Weliana; Raharjo, Dwi; Hartanti, Lucky (Fakultas Pertanian Universitas Tanjungpura, 2020)
This study aims to determine the formulation of the use of cassava starch and gelatin on the physicochemical and organoleptic properties of marshmallows. This study used a Randomized Block Design (RBD) by 1 factor consisting of 7 levels formulation of cassava starch concentration. Each treatment was repeated 4 times to obtain 28 combination samples. Parameters of observation included water content, ash content, texture, total dissolved solids, and sensory. Effectiveness Index Test results showed that the best concentration was found in the best concentration was found in the addition of 4.65g cassava, 19,85g gelatin starch concentration, by the physcochemical and scusory properties water content was 19,93%, ash content was 1,62%, texture was 0,025kg, total dissolved solids were 26,30 °Brix. The best sensory test results were 4,72 (likes) sweetness, 4,72 (likes) texture, 4,72 (likes) color and 4,68 (likes) elasticity. Keywords: Cassava Starch, Formulations, Gelatin, Marshmallows